2010
DOI: 10.4321/s1130-01082010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor and chronic hepatitis C

Abstract: Objective: the hepatocyte growth factor (HGF) is a pleiotropic cytokine produced by hepatic stellate cells and implicated in liver regeneration and fibrosis. Serum levels of HGF vary in liver diseases, reflecting hepatic damage and hepatocellular dysfunction. In this study, serum levels of HGF and the relationship between HGF and biochemical, histological and virological data, have been analysed in patients suffering from chronic hepatitis C (CHC). Patients and methods: serum HGF concentration was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The studies performed in patients with chronic hepatitis C have demonstrated that higher HGF concentrations were associated with increased fibrosis [ 10 ] and angiogenesis [ 11 ] and have indicated a higher risk of development of hepatocellular cancer [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies performed in patients with chronic hepatitis C have demonstrated that higher HGF concentrations were associated with increased fibrosis [ 10 ] and angiogenesis [ 11 ] and have indicated a higher risk of development of hepatocellular cancer [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 27 Furthermore, patients with chronic hepatitis C have also proved that higher HGF concentrations were correlated with increased fibrosis and angiogenesis and have indicated a higher risk of PLC development. 28 31 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several assay panels are currently available for the assessment of fibrosis, which use a combination of markers, including GGT. GGT is associated with hepatocyte growth factor, which is a pleiotropic cytokine produced by hepatic stellate cells ( 37 ). Therefore, early cholestasis or an increase in epidermal growth factor expression may offer an explanation for the observed increase in GGT with increasing fibrosis severity.…”
Section: Discussionmentioning
confidence: 99%